2022
DOI: 10.3390/plants11030341
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil Inoculation with Bacillus amyloliquefaciens FZB42 on the Phytoaccumulation of Germanium, Rare Earth Elements, and Potentially Toxic Elements

Abstract: Bioaugmentation promises benefits for agricultural production as well as for remediation and phytomining approaches. Thus, this study investigated the effect of soil inoculation with the commercially available product RhizoVital®42, which contains Bacillus amyloliquefaciens FZB42, on nutrient uptake and plant biomass production as well as on the phytoaccumulation of potentially toxic elements, germanium, and rare earth elements (REEs). Zea mays and Fagopyrum esculentum were selected as model plants, and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…All these remediation techniques have certain merits and drawbacks, as they leave secondary residual effects in soils. Nonetheless, phytoremediation (use of accumulator plants in soil cleaning) presents the least harmful effects, cost-effective amongst other techniques and suits the increasing quest for environmental sustainability [4,[18][19][20][21]. Phytoremediation may be grouped based on their operating mode and they include; phytoextraction, phytostabilisations, phytofiltration, phytodegradation, phytovolatilisation, and rhizodegradedation [22].…”
Section: Introductionmentioning
confidence: 99%
“…All these remediation techniques have certain merits and drawbacks, as they leave secondary residual effects in soils. Nonetheless, phytoremediation (use of accumulator plants in soil cleaning) presents the least harmful effects, cost-effective amongst other techniques and suits the increasing quest for environmental sustainability [4,[18][19][20][21]. Phytoremediation may be grouped based on their operating mode and they include; phytoextraction, phytostabilisations, phytofiltration, phytodegradation, phytovolatilisation, and rhizodegradedation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its strong potential in this field, this technique must be deepened and tested. The effect of the application of the commercial product RhizoVital ® 42, containing Bacillus amyloliquefaciens FZB42, on soil polluted by potentially toxic elements (PTEs), critical raw materials (CRMs, such as germanium -Ge), and rare earth elements (REEs) was the object of the study by Okoroafor et al [6]. Results showed that B. amyloliquefaciens successfully integrated (relative abundance 1%) into the bacterial community, which was not altered by the enrichment.…”
mentioning
confidence: 99%